Inovasi Produk Olahan Pisang sebagai Strategi Pengembangan Ekonomi Masyarakat Desa Purba Lamo Kecamatan Lembah Sorik Marapi - Nur Ainun; Muslim Hasan; Nova Elliza; Asril Fauzi; Juliana Syafitri; Mariatun Khoiriah Rambe; Riski Hidayah; Aulia Rizki Pulungan; Putri Salsabila; Ici Lassie Rahmah Rama Dhani (Lembaga Pengembangan Kinerja Dosen, 2025)
The Community Service (KKN) program group 38 in Purba Lamo Village, Lembah Sorik Marapi Subdistrict, aims to enhance the community's economy through product diversification based on local potential, specifically bananas. Although the village produces an abundance of bananas, its processing has been limited to selling them in raw form or simple processed products, resulting in low added value. The KKN program initiated training on processing bananas into chips with various flavors, introducing modern packaging techniques and adaptive marketing strategies. The approach used was participatory, including socialization, direct practice, and continuous mentoring in production and distribution. The results showed an improvement in the residents' skills in product processing, the emergence of new entrepreneurial motivation, and collective initiatives to expand marketing networks at local and regional levels. The long-term impact of this activity is an increased awareness among the community about the importance of managing local potential innovatively, which supports collective welfare. This KKN program not only provides short-term benefits, such as increased income, but also contributes to strengthening the village's economic independence sustainably.